A long-term dataset of in-situ temperature data reveals wind-induced up- and downwelling in the coastal waters of Nha Trang, South Central Vietnam - Kunzmann, Andreas; Du, Hoang Trung; Brefeld, David; Pinter, Sina; Pohlmann, Thomas (Vietnam Journal of Marine Science and Technology, 2024)
In order to implement successful coastal management and protect corals, it is imperative to understand the Nha Trang Bay’s coastal processes and take adequate measures to protect corals and reef structure. This paper aimed to analyze whether sudden variations in physical parameters, such as temperature, could be potentially harmful to coastal coral reefs, in addition to anthropogenic factors such as pollution and intensive fishing. In this paper, the first long-term observation (2008–2019) of temperatures, not only from SST data, but also in situ in coral reefs (10 and 18 m depth) at Nha Trang Bay, South Central Vietnam, was investigated. The data showed that wind-induced upwelling during summer mainly govern the coastal region. In contrast, wind-induced downwelling was found during winter, visible in all three investigated water layers (SST, 10 and 18 m). In winter, the vertical mixing is strong and there is virtually no time-lag between the layers. In summer a scattering layer was formed, the phenomenon where a layer of water with different properties (such as temperature or salinity) is formed, blocking the sinking of water. In summer, correlations with air temperature were not significant, nor were correlations with night cooling, thus having implications for the distribution of nutrients and the health of the coral reefs. However, this was only the situation near the coast. Wavelet analysis shows that the short-term variability is significantly more substantial, caused by the shallow depth of the thermocline, which is much stronger affected by tidal and weather events than in winter. As a result of the combination of large yearly temperature variations (21oC to 31oC) plus increased sediment deposition in the rainy seasons, reefs close to the shore are generally not well-developed. This paper strongly advocates for science-based monitoring of coral reef conditions and underscores the need for law enforcement within the Marine Protected Area of Nha Trang Bay.